Arf6 controls retromer traffic and intracellular cholesterol distribution via a phosphoinositide-based mechanism - Catherine Marquer (Nature Portfolio, 2016)
The small GTPase Arf6 regulates intracellular transport, phosphoinositide signalling and cholesterol homeostasis. Here, Marquer et al. show that loss of Arf6 causes cholesterol accumulation in endosomes due to defects in phosphoinositide-dependent retromer-mediated trafficking of CI-M6PR and NPC2.